ASAPPP
what is the domain and range?
Answer:
domain refers to the set of possible input values, the domain of a graph consists of all the input values shown on the x-axis. The range is the set of possible output values, which are shown on the y-axis
Help
Help help pls I can’t answer this
Answer:
A
Step-by-step explanation:
1/6^2 =
1/36
Answer:
B
Step-by-step explanation:
When you divide 2 numbers with the same base, you subtract the exponents. We know fractions are basically division, so we would do 3-5. You get -2 as your exponent and we know negative exponents can be written two ways: [tex]6^{-2} and \frac{1}{x6^{2} }[/tex]. Both of those are there, so they are not the correct answer. B can be determined as the one not because the exponent is positive.
A triangle has sides with lengths of 6 centimeters, 5 centimeters, and 3 centimeters. Is it a right triangle?
Answer:
No
Step-by-step explanation:
A triangle with a side of five is only a perfect right triangle when it's in a 5,12,13 ratio.
Furthermore, to check, 5^2 is 25 and 3^2 is 9. 25+9 is 34, which doesn't not have a square root of 6.
(x^3 + 8x^2 + kx + 4) ÷ (x+ 2)
Please help how do i solve for k please include steps this is called remainder theorem
Answer: 14
Step-by-step explanation:
Check it
Answer:
k = 14
Step-by-step explanation:
The Remainder theorem states that if f(x) is divided by (x + h) then the remainder is f(- h)
If (x + h) is a factor of f(x) then the remainder is zero, that is f(- h) = 0
Given (x + 2) is a factor of f(x) then f(- 2) = 0, that is
(- 2)³ + 8(- 2)² - 2k + 4 = 0
- 8 + 8(4) - 2k + 4 = 0
- 8 + 32 - 2k + 4 = 0
- 2k + 28 = 0 ( subtract 28 from both sides )
- 2k = - 28 ( divide both sides by - 2 )
k = 14
The smaller triangle was dilated to form the larger triangle. What is the value of x? A smaller triangle has side lengths of 3 and 5. A larger triangle has side lengths of 9 and x + 1. 10 11 14 15
Answer:
14 is the answer
Step-by-step explanation:
I hope I helped
The value of x is 14.
The correct option is C.
What is ratio?The ratio is a numerical relationship between two values that demonstrates how frequently one value contains or is contained within another.
Given:
The smaller triangle was dilated to form the larger triangle.
A smaller triangle has side lengths of 3 and 5.
A larger triangle has side lengths of 9 and x + 1.
That means,
the ratio,
3/5 = 9/(x + 1)
3x + 3 = 45
x = 14
Therefore, the value is 14.
To learn more about the ratio;
https://brainly.com/question/13419413
#SPJ6
im so confused please help
Answer:
9
Step-by-step explanation:
It's just telling you that the value of x is 3, so in the equation,
you replace x with 3,
2(3) + 3,
2 x 3 = 6,
6+ 3 = 9
Answer:
9
Step-by-step explanation:
They give you the equation:
2x+3
And they give you the (x):
x=3
So you simply replace (x) with 3
2x+3
2(3)+3
now solve
2•3= 6
6+3 = 9
9 is your answer.
Hope this helps! If you have any questions on how I got my answer feel free to ask. Stay safe!
Lizet bought a bag of gummy bears and ate one-third of them. The next day, she ate 16 more gummy bears. If she ate a total of 37 gummy bears, how many were originally in the bag?
Answer:
im trying to figure out the same thing
Step-by-step explanation:
I need help please..
Angle PQR is a straight angle.
The measure of angle SQR is 25°.
The measure of angle PQS is xº.
What is the value of x?
Answer:
x=155
Step-by-step explanation:
since its a straight line, it has to equal 180 in total.
SQR is 25, so to find PQS you subtract 180-25
Which equals 155
The ratio of green to red jelly beans in a jar is 4 to 6. If there are 28 green jelly beans, how many total green and red jelly beans would be in the jar?
4 x 7 = 28
6 x 7 = 42
42 is the answer UvU
Answer:
76 jelly beans total
Step-by-step explanation
4 x 8 = 28
6 x 8 = 48
28 + 48 = 76
A circle is tangent to the line given by the equation 3x-y= 15 at the point (9,12). The center of the radius falls on the line given by 2y+x=8. Find the equation of the circle and identify its center and radius
Answer:
The equation of the circle is x² + y² + 12x - 14y - 165 = 0 , its center is (-6, 7) and its radius is 5√10 units.
Step-by-step explanation:
a. The center of the circle
Since the equation of the tangent of the circle is 3x - y = 15, we write it in standard form. So y = -3x - 15. Its gradient is -3. The perpendicular line tot he tangent is the radius and it passes through the center of the circle and the point (9, 12). For two perpendicular lines of gradient m₁ and m₂, m₁m₂ = -1. If m₁ = -3, then m₂ the gradient of our radius line is gotten from m₁m₂ = -1
m₂ = -1/m₁ = -1/-3 = 1/3
Since the radius also passes through the point (9, 12), its equation is gotten from
(y - y₁)/(x - x₁) = m₂ where (x₁, y₁) = (9, 12)
Substituting the value of the variables into the equation, we have
So, (y - 12)/(x - 9) = 1/3
cross-multiplying, we have
3(y - 12) = (x - 9)
expanding the brackets, we have
3y - 36 = x - 9
collecting like terms, we have
3y = x - 9 + 36
3y = x + 27
So, the equation of the radius line is
3y - x = 27.
Now, since the center of the circle lies on the line 2y + x = 8, the radius line and this line intersect at the center of the circle. So, we solve both equations simultaneously to find the center of the circle.
So, 3y - x = 27 (1)
2y + x = 8 (2)
adding (1) and (2), we have
5y = 35
y = 35/5
y = 7
Substituting y = 7 into (2), we have
2y + x = 8
2(7) + x = 8
14 + x = 8
x = 8 - 14
x = -6
So, the center of the circle is at (-6, 7)
b. The radius of the circle
The radius of the circle is the length of the line from the tangent point to the center of the circle. So, r = √[(x₂ - x₁)² + (y₂ - y₁)²] where (x₁, y₁) = (-6, 7) and (x₂, y₂) = (9, 12).
Substituting these into r, we have
r = √[(9 - (-6))² + (12 - 7)²]
= √[(9 + 6)² + (12 - 7)²]
= √[15² + 5²]
= √[225 + 25]
= √250
= √25 × √10
= 5√10 units
c. The equation of the circle
Now, the equation of a circle with center (h,k) and radius, r is
(x - h)² + (y - k)² = r² where (h. k) = (-6,7)
Substituting the variables into the equation, we have
(x - (-6))² + (y - 7)² = (√250)²
(x + 6)² + (y - 7)² = 250
expanding the brackets, we have
x² + 12x + 36 + y² - 14y + 49 = 250
collecting like terms, we have
x² + y² + 12x - 14y + 36 + 49 - 250 = 0
x² + y² + 12x - 14y - 165 = 0
So, the equation of the circle is x² + y² + 12x - 14y - 165 = 0 , its center is (-6, 7) and its radius is 5√10 units.
Given: BC ≅ CD and AC bisects ∠BCD
Prove: ∆ABC ≅ ∆ADC
Please show work and don't just put random letters like the first time i asked this PLEASE i really need this
License plates in a particular state display 2 letters followed by 4 numbers How many different license plates can be manufactured for this state?
Answer:6,760,000
Step-by-step explanation:
What is the slope-intercept form of the linear equation 2x + 3y = 6? Drag and drop the appropriate number, symbol, or variable to each box.
Answer:
[tex]y=-\frac{2}{3}x+2[/tex]
Step-by-step explanation:
y = -2/3 x + 2
Answer:y=-2/3x+2
Step-by-step explanation:
Trust me
Simplify the following by combining like terms:
-5- x+4x - 4
How to calculate slope of a line STEP-by-STEP
Do not spam
If you spam I will report!
Step-by-step explanation:
You want to start by looking for two coordinates and decide which ones you'll use.
Then you want to find the difference between the two y coordinates also known as the rise.
Then you'll want to find the difference between the two x coordinates also known as the run.
After that you'll want to divide the difference of the two y coordinates with the difference of the x.
Hopefully this helps, much love.
Chart given to best illustrate.
[tex]8-4/4-2=4/2=2[/tex]
8 is from the right side which is subtracted by the 4 in the left equation. Then you divide that by 4 with 2 which results in 2. You end up with 4/2 and bingo!
2
Step-by-step explanation:
do you have a graph or points
graph it is rise over run wich is y/x
and if its points then you do y1-y2/x1-x2
If your cell phone bill is $85.87 and there is a 8.4% late fee, how much will your bill be if it's late?
Answer:
Step-by-step explanation:
If you're late on your cell phone bill, you'll generally be fined as much as 5 percent of the amount due or $5, whichever is higher. Late charges may not kick in immediately. At AT&T, for example, the fee is applied six days after your due date. Often, your late fee will be subject to taxes.
Answer:
7.21308 is the late fee so in total it is going to be 98.08308
Step-by-step explanation:
Your welcome
solve for u
Simplify your answer as much as possible.
I need some help on solving this problem
Answer:
J. 80°
Step-by-step explanation:
PLEASE ANSWER!! WILL MARK BRAINLIEST
Now that Anna's Boutique has merged with another store, the members of its staff make $26. That is 30% more than they historically made. How much did the staff members use to make per hour?
Answer:
20
Step-by-step explanation:
30% of 20 is 6
I need ur help ASAP plsssssss first right answer gets brainliest
Answer:
21
Step-by-step explanation:
Expand & simplify
5
(
p
+
6
)
−
5
(
p
−
2
)
Answer:
Expanded form - write 5 ( p+6 ) - 5 ( p - 2)
as an equation y = 5 (p+6) -5(p-6)
simplifyed form - 40
Step-by-step explanation
Graeme earns $4.23 for each half hour that he works. How much will he make after 4 hours of work?
Answer:
[tex]4.23*8=33.84[/tex]
Graeme will make $33.84 after four hours of work.
I need these pls!!!!!
Answer:
1) $38.40 2) $255. 3) $5.80 4) $3.12
Step-by-step explanation:
So you have to multiply the years by the amount of money you have. Then you multiply that by the percent and divide by 100. (For the last one: because its a month you have to make it a fraction so it was 8/12)
NEED THIS ANSWER BY THE END OF THE DAY PLEASE HELP !!
A party rental company has chairs and tables for rent. The total cost to rent 5 chairs and 3 tables is $32. The total cost to rent 2 chairs and 12 tables is $83. What is the cost to rent each chair and each table ?
Answer: So the cost to rent each chair is $1.25 and the cost to rent each table is $8.50
Step-by-step explanation:
Let C = cost to rent each chair
Let T = cost to rent each table
4C + 8T = 73
2C + 3T = 28
Multiply the 2nd equation by (-2) and then add the equations together
4C + 8T = 73
-4C - 6T = -56
2T = 17
T = 17/2 = 8.5
Plug this in to the 1st equation to solve for C
4C + 8(17/2) = 73
4C + 68 = 73
4C = 5
C = 5/4 = 1.25
Which function best represents this graph?
Answer:
who tell me how to start?
A salespersons commision varies directly with their sales. For $1000 in sales, the commission is $85. What is the constant of variation? What is the commission for $2300 in sales?
Forget that last one I posted I need this pls
I NEED HELP!!!! WITH NUMBER 9, & 10??
Answer:
awnser one is 7 and question 2 is -10
Step-by-step explanation:
−12−2−−55=? question one
In the first fraction, the negative numerator and negative denominator cancel each other.
Since the the second fraction is negative and you are subtracting, remove the negative sign and switch the operation to addition.
The equivalent equation is
122+55=?
The fractions have unlike denominators. First, find the Least Common Denominator and rewrite the fractions with the common denominator.
LCD(12/2, 5/5) = 10
Multiply both the numerator and denominator of each fraction by the number that makes its denominator equal the LCD. This is basically multiplying each fraction by 1.
(122×55)+(55×22)=?
Complete the multiplication and the equation becomes
6010+1010=?
The two fractions now have like denominators so you can subtract the numerators.
Then:
60+1010=7010
Since 70 divided by 10 equals 7 then,
7010=7
Therefore:
−12−2−−55=7
Question 2
−81+6−3=?
In the second fraction, move the negative sign from the denominator to the numerator and the value remains the same.
The equivalent equation is
−81+−63=?
The fractions have unlike denominators. First, find the Least Common Denominator and rewrite the fractions with the common denominator.
LCD(-8/1, -6/3) = 3
Multiply both the numerator and denominator of each fraction by the number that makes its denominator equal the LCD. This is basically multiplying each fraction by 1.
(−81×33)+(−63×11)=?
Complete the multiplication and the equation becomes
−243+−63=?
The two fractions now have like denominators so you can add the numerators.
Then:
−24+−63=−303
Since -30 divided by 3 equals -10 then,
−303=−10
Therefore:
−81+6−3=−10
Solution by Formulas
Apply the fractions formula for addition, to
−81+6−3
and solve
(−8×−3)+(6×1)1×−3
=24+6−3
=30−3
=−10
HELP ME OUT PLZ PLZ
Answer:
SAS
Step-by-step explanation:
The information represents a Side, Angle, Side triangle
Answer:
SAS !
Step-by-step explanation:
it means Side, Angle & Side triangle and it does show that :)